Gulf Between Higher and Weaker Sections of Society - Chaudhary, Shivani; Mohan, Mayank (Journal of Commerce and Trade, 2009)
An expansion of money supply upto the point of full employment may not be harmful for the economy. In fact, mild inflation may even serve as a tonic for the economy of the country. But an expansion of money supply after the point of full employment certainly degenerates into runaway or hype-inflation and thus is very harmful for the economy of a country. It creates business uncertainty which is harmful to production. In fact, hyper-inflation disrupts the smooth functioning of the economy. When the whole global market is facing the problem of economic depression, our country is also not an exception to that. Though the situation is not that much critical as in American and European countries. But the question is;Is this economic depression benefiting India? To some extent it is true. There is large scale inflation in our country because of which the number of millionaires is increasing day by day. Also the number of poor is increasing. The rate at which inflation is increasing the dreadful gulf of inequality is also digging up in our society. It is a big question; what will be the economic picture of our country in the forthcoming years?